Information Disclosure and Sustainable Competitive Advantage: Evidence from the Spanish Tourism Industry - Camisón-Haba, Sergio; Gonzales-Cruz, Tomas; Clemente-Almendros, José Antonio (Sustainability, 2023)
Of all the resources and capabilities that have a well-established impact on decision-making, information stands out. With the advent of the digital economy, organizations have been making significant information and communication technology (ICT) investments, but the empirical evidence of the impact of these investments on business outcomes has been inconsistent. This article studies the conditions that disclosed information resources and ICT must fulfil in order to become a source of sustainable competitive advantage in tourism organizations. The results point to the need to identify distinct financial and non-financial information dimensions, distinguished according to their direct potential for creating and maintaining competitive advantages through the improvement in relations with various stakeholders.
Keywords: information asymmetries; information technologies; digitization; reputation; financing capacity; stakeholders; JCR; Scopus